Arid1a promotes thymocyte development through β‐selection‐dependent and β‐selection‐independent mechanisms. Issue 4 (27th December 2021) - Yang, Xiaofeng; Wang, Xin; Lei, Lei; Su, Yanhong; Zou, Yujing; Liu, Haiyan; Jiao, Anjun; Zhang, Cangang; Liu, Jun; Li, Wenhua; Ding, Renyi; Zhou, Xiaobo; et al.
Abstract: Early T‐cell development from CD4 − CD8 − double‐negative (DN) stage to CD4 + CD8 + double‐positive (DP) stage in the thymus is regulated through multiple steps involving a batch of sequentially expressed factors. Our preliminary data and a recent report showed that AT‐rich interaction domain 1A (Arid1a) is required for the transition from DN to DP stages, but the mechanism is not fully understood. In this study, we consolidated that conditional deletion of Arid1a in T‐cell lineage intrinsically caused developmental blocks from DN3 to DN4 stages, as well as from DN4 to DP stages using both in vivo adoptive T‐cell transfer model and in vitro culture system. The expression of intracellular TCRβ is significantly decreased in Arid1a‐deficient DN4 cells compared with WT cells. OT1 transgenic TCR can rescue the defect in the transition from DN3 to DN4 stages, but not from DN to DP stages. Furthermore, we observed a comparable or stronger proliferation capacity accompanied by a significant increase in cell death in Arid1a −/− DP cells compared with that in WT controls. RNA‐Seq analysis shows a significant enrichment of apoptotic pathway within differentially expressed genes between Arid1a −/− and WT DP cells, including the upregulation of Bim, Casp3 and Trp53 and the downregulation of Rorc, Bcl ‐ XL and Mcl1 . Therefore, our study reveals a novel mechanism that Arid1a controls early T‐cell development by maintaining intracellular TCRβ expression‐mediated β‐selection and activating parallel cell survival pathways.